Assessment of Potential drug-drug interactions among hospitalized patients - Mohammed Salem Al beladai,; Inad Adel Alharbi,; Fahad Abdullah Alharbi,; Mohammed Kaseb Alanazi,; Meshal Khaled Alawn,; Mohammed Menahi Alshabi,; Sami Dakhel Saad Almatrafi,; Badr Hegy Abdullah Alaqel,; Kadhem Habib Kadhem Alsayafi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Drug-drug interactions (DDIs) are a significant contributor to preventable adverse drug events and associated health complications, especially in patients receiving polypharmacy. DDIs have been shown to contribute to hospital admissions and adverse drug reactions, making their identification and management crucial. This study aimed to assess the frequency, severity, and associated factors of potential DDIs (pDDIs) in patients admitted to internal medicine wards of a large teaching hospital. Methods: A cross-sectional study was conducted at a large teaching hospital. Patients admitted to various internal medicine wards were included, and data on prescribed medications, patient demographics, and hospital stay were collected from medical records. The severity of potential DDIs was assessed using Lexi-Comp and Micromedex databases. Logistic regression was employed to analyze associations between pDDIs and factors such as age, gender, length of hospital stay, and the number of medications prescribed. Results: A total of 448 patients were included, with 73.3% prescribed more than four medications. A total of 3,350 potential DDIs were identified, with moderate interactions being the most common (60.9%), followed by major interactions (48.8%) and minor interactions (28.8%). The average patient was exposed to 7.6 potential DDIs, and 11.8% of patients had at least one pDDI. A significant association was found between the occurrence of pDDIs and the prescription of seven or more medications (OR: 0.048, p < 0.0001). No significant associations were observed with age, gender, or length of hospital stay. Conclusion: Polypharmacy is a key risk factor for potential DDIs in hospitalized patients, with moderate and major interactions being the most common. Efforts to reduce the prescription of multiple medications and implement clinical pharmacy systems are essential to mitigate the risk of DDIs and improve patient safety in hospital settings.